If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+1)=6x-20
We move all terms to the left:
4(2x+1)-(6x-20)=0
We multiply parentheses
8x-(6x-20)+4=0
We get rid of parentheses
8x-6x+20+4=0
We add all the numbers together, and all the variables
2x+24=0
We move all terms containing x to the left, all other terms to the right
2x=-24
x=-24/2
x=-12
| 8x+27-12x=73 | | 8(4+6x)+2=178 | | Y=—6x+5 | | -4=x-(5 | | 15=–2f+3 | | u+41–8=6 | | -9-18q=-153 | | 6=g5 | | a=7/3(28)+52/10 | | 5(x+4)=2(2x+5)+6 | | 8n=4n-10 | | 3÷x-4=2 | | r/11=143 | | (11x-6)=(4x+13) | | `2(x-4)+3x=5x+2` | | j3=2 | | -6-5z=14 | | 42=32+x/5 | | 12x-24+3x=1/2x=3+2 | | 2d+8=-22 | | 12x-24+3x=1/2x=3=2 | | 9=f3 | | -2h-8=16 | | 14=n/54 | | 12-3x=7+10x | | 3j−7=2 | | 4x-5=13x+11 | | 9=f3 | | 3y-3=3y+1 | | (17y-9)=180 | | 8(4-2x)=4(3-5x)4x | | −5(3x−5)=2(x−31)−117 |